2019
DOI: 10.1108/apjml-10-2018-0408
|View full text |Cite
|
Sign up to set email alerts
|

Co-production strategy, retail competition, and market segmentation

Abstract: Purpose The purpose of this paper is to examine the effect of manufacturers’ co-production strategy on market segmentation and channel performance under retail competition. Design/methodology/approach It differs from previous empirical studies by primarily focusing on the increment in consumer value accompanying co-production. The authors establish a game-theoretical model to analyze the impact of co-production on market segmentation and the profitability of channel members in a competitive retail environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The main stream of the literature on this topic focuses on whether and when encroachment could benefit downside retailers. Conventional wisdom indicates that upside firm encroachment in supply chains benefits the encroacher by competing directly with its end-retailers in the market, but it harms the endretailers by creating competition (Hendershott and Zhang, 2006;Liu and Zhang, 2006;Pan, 2018;Du et al, 2018;Wang and Fan, 2020). For example, Pan (2018) examined encroachment under the framework of a two-part tariff contract and showed that when a monopoly manufacturer supplies competing retailers and contracts are offered secretly, encroachment may aggravate double marginalization in supply chains, thereby leading to increased unit prices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main stream of the literature on this topic focuses on whether and when encroachment could benefit downside retailers. Conventional wisdom indicates that upside firm encroachment in supply chains benefits the encroacher by competing directly with its end-retailers in the market, but it harms the endretailers by creating competition (Hendershott and Zhang, 2006;Liu and Zhang, 2006;Pan, 2018;Du et al, 2018;Wang and Fan, 2020). For example, Pan (2018) examined encroachment under the framework of a two-part tariff contract and showed that when a monopoly manufacturer supplies competing retailers and contracts are offered secretly, encroachment may aggravate double marginalization in supply chains, thereby leading to increased unit prices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Wang et al (2022) used the Stackelberg game to describe the channel members' decision sequence in a three-echelon supply chain. Also, Wang and Fan (2020) stablished a game-theoretical model to analyze the profitability of channel members in a competitive retail environment. Du et al (2018) took the Stackelberg game to model the interaction between the service providers.…”
Section: Opaque Selling In a Supply Chainmentioning
confidence: 99%
“…In this system, channel members, for the purpose of the maximization of their profits, will make decisions in favor of themselves according to their strength, scale and ability to serve consumers, which will inevitably bring about the amplification, delay and shock of demand information in the channel. Even the irrational behavior of the members of the supply chain system will lead to serious channel conflicts (Wang and Fan, 2019; Li et al , 2019a, b; Lu and Chen, 2013; Du et al , 2018), affect interfirm relations, and greatly reduce the efficiency of the entire supply chain. At the same time, for the consumers' demand, they often have different psychological price expectations because of the difference in the acceptance of network channels, which leads to the conflict between the network direct sale channel and the offline traditional retail channel.…”
Section: Introductionmentioning
confidence: 99%